(untitled) (Costos y Gestión, 2024)
Due to the importance of investments in the performance of firms, this work proposes two objectives: to describe the evolution of the profitability of manufacturing companies in Uruguay in 2010-2017, and to verify to what extent this profitability depends on changes in the size and cost structure of companies, that is, identifying the mechanism that pulls between size and profitability. To do this, it uses an accounting database of 595 manufacturing companies. The results obtained show, first of all, that the Uruguayan industry has experienced a continuous decrease in its profitability, in all areas. Secondly, predominantly, the increase in business size has led to a negative effect on profitability. This effect operates through an increase in the relative weight of costs in income and a decrease in stock rotation. As a by-product of the main research, when using the quintile stratification technique, it was observed that the signatures of the largest stratum are on average 10 times larger than those of the lower stratum and 44 times larger on average than those of the remaining three strata.